Saving the Moving Position on the Continuous Passive Motion Machine for Rehabilitation of Shoulder Joints - Antonius Hendro Noviyanto (Universitas Sanata Dharma, 2019)
This paper presents the results of the motion therapy device Continuous Passive Motion (CPM) Machine which is applied to the shoulder joint with storage movement. The process of joint rehabilitation is carried out by continuous passive movements. This movement is intended not to overload the work of the muscles and there is no stiffness in the joints after surgery or stroke patients or patients who have carried out immobilization for quite a long time. The CPM Machine developed can move flexion and horizontal abduction. The position storage in this tool is carried out in a range of movements in flexion and horizontal abduction. So that with the storage of movement can be done movement / therapy exercises in patients with joint stiffness passively and continuously.